Student learning independence using the application of the recitation method during online learning through the Google Classroom App - Riawati Azizah (IAIN Salatiga, 2021)
In an effort to reduce increasing number of Covid-19 spread, currently, majority ofstudents from early childhood education to universities are undergoing online learning. There are various learning management systems (LMS) as well as social media digital platforms that can be utilized by teachers and students to carry out online learning, one of which is Google Classroom. By applying the recitation or assignment method through Google Classroom, it is found that student learning independence has not been formed optimally. This research aims to describe how student learning independence is viewed from the application of the assignment method in the specific case of Islamic education subject during online learning through Google Classroom. This is descriptive qualitative research which collects data from interviews with six subjects who regularly use Google Classroom application as a learning medium and assignments. The six subjects interviewed consist of teachers and college students. This study shows that Google Classroom is considered quite effective as an assignment medium because it could be accessed anywhere and anytime and saved storage. However, in terms of independencestudent skill, it is tend to not work as expected. Therefore, more efforts are required by the teachers to give students motivation and increase the awareness to develop independent learning skills of students.